2020
DOI: 10.3390/antibiotics9110759
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Antibiotic Resistance: Public Awareness Survey in the Republic of Cyprus

Abstract: We aimed to assess the knowledge and understanding of antibiotic use and resistance in the general population of Cyprus, in order to inform future antibiotic awareness campaigns with local evidence. Cross-sectional survey following the methodology of the “Antibiotic resistance: Multi-country public awareness survey” of the World Health Organization, during December 2019–January 2020. A total of 614 respondents participated: 64.3% were female and most were aged 35–44 years (33.2%) or 25–34 years (31.8%). One-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
(36 reference statements)
4
19
0
2
Order By: Relevance
“…From the ordinal logistic regression analysis, the main determinants of knowledge about antibiotics were age and majors, and suggests that, if there are limited resources, educational programs on antibiotics should be targeted at younger students from programs that are non-life sciences based. The finding that respondents from the medical or life sciences majors had significantly better knowledge than students from the other courses is in line with previous studies [ 20 , 21 , 22 ]. As expected, those students had more exposure to scientific knowledge related to antibiotics and ABR compared with students from other majors.…”
Section: Discussionsupporting
confidence: 91%
“…From the ordinal logistic regression analysis, the main determinants of knowledge about antibiotics were age and majors, and suggests that, if there are limited resources, educational programs on antibiotics should be targeted at younger students from programs that are non-life sciences based. The finding that respondents from the medical or life sciences majors had significantly better knowledge than students from the other courses is in line with previous studies [ 20 , 21 , 22 ]. As expected, those students had more exposure to scientific knowledge related to antibiotics and ABR compared with students from other majors.…”
Section: Discussionsupporting
confidence: 91%
“…More than half (64%) had the misconception that antibiotics are effective against viral infections; 32% believed that they should stop their prescribed course of antibiotics when they feel better, and 76% mistakenly thought that AMR is due to the human body, instead of bacteria, becoming resistant to antibiotics [ 6 ]. Several other studies reported similar observations due to poor antibiotic and AMR knowledge among the general public [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Population-based educational campaigns, however, have been found to have either mixed or no effect on improving knowledge and appropriate antibiotic practices, suggesting a need for more targeted approaches in tailoring education for specific sub-populations [ 16 , 17 ].…”
Section: Introductionsupporting
confidence: 57%
“…Nonetheless, Riyadh PPS had better knowledge about the completion of the antibiotic course. This could be attributed to the notion that big cities’ population dwellings are more aware of such issues [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%